La gratuità si paga Le metamorfosi nascoste del lavoro - Greppi, Spartaco (Edizioni Casagrande, 2022)
From riders to interns, from freelancers to part-time workers: employment today is increasingly flexible and precarious. With the tools of social inquiry, the authors present a critical picture of the phenomenon of the so-called "free work" in Switzerland, that is a job rendered in the absence of corresponding remuneration.